ANALISIS UJI KARAKTERISTIK BIOETANOL DARI PISANG HUTAN TERHADAP VARIASI MASSA RAGI - Dady Sulaiman; St Syahdan; Siti Maria Ulva (Jurnal Kumparan Fisika, 2021)
Biomass is one of the solutions for Indonesia to obtain energy because Indonesia has the potential for biomass like biodiesel and bioethanol. The biomass to be studied is Bioethanol. One of the main ingredients in the manufacture of bioethanol is forest bananas, where this type of banana is very easy to find in rural areas around the district of Bulungan. Forest bananas are a type of wild plant that grows in the forest and it’s not consumed by residents because there are many seeds in the banana. Therefore, forest banana waste is increasing due to the lack of utilization of the waste. Based on these problems, it is necessary to conduct research that aims to test the characteristics of bioethanol from forest bananas to the variation of yeast mass. The stages of the research method that will be done include several stages, namely 1) the manufacture of bioethanol, 2) the stage of measuring ethanol levels, and 3) the stage of testing the characteristics of bioethanol. The stages of bioethanol testing are characteristic tests, including: 1) Ethanol Content Analysis, 2) Water Content Analysis, 3) Density Analysis, 4) Specific Gravity and API Gravity Analysis, 5) Heat Value Analysis. Based on the research results obtained, the quality of bioethanol produced has the value of density and specific gravity in accordance with the quality standard of bioethanol which is 0.78 in yeast 3% of raw materials. The caloric value that has a close relationship with API Gravity is close to the maximum value of the bioethanol quality standard which is 3702.30 kcal/kg in yeast of 5%. The value of the largest ethanol content was obtained at the total yeast content of 5% which is 24.8%. The lowest water content value is obtained at the total yeast content of 3% which is 75%.